Estimation de la densité par comptage des nids des Bonobos (Pan paniscus) dans la région de Bolobo des localités de Nkala et Embirima, République Démocratique du Congo : résultats préliminaires - Ulrich Maloueki; Simon‑Pierre Kumugo Ndimbo; Jean Mukulire Malekani; Bekeli Nseu Mbomba (Revue de Primatologie)
The Territory of Bolobo (Province of Bandundu, R.D. Congo) is located at 300 km in the North-West of Kinshasa, along the Congo River. In this study, we researched the bonobos distribution, Pan paniscus (Pongidae, Primates), in their origin location from Bolobo. We determined the densities of the populations of bonobos in the mosaics of forests intersected with savannas in this area. The densities estimated during September 2008, have been relatively low 0.04 to 0.21 bonobos/km2, by the method of nests counting, along the transects lines, respectively for the secondary forest of Nkala-MMT (Mbou-Mon-Tour) and the primary forest of Embirima. Concerning the rate of bonobo nests expressed as their kilometric index of abundance (KIA) it has been of 49.11 nests/km in Embirima, higher than that of Nkala-MMT where the KIA was of 12.71 nests/km. These data show that bonobos are distributed in a very scattered and irregular way. These observations may help establishing an adequate program of survey for the saving and the protection of the specie.